2013
DOI: 10.3390/jpm3010014
|View full text |Cite
|
Sign up to set email alerts
|

Driving Forces Behind the Past and Future Emergence of Personalized Medicine

Abstract: Personalized medicine can be seen as a continuously developing approach to tailoring treatments according to the individual characteristics of a patient. In some way, medicine has always been personalized. During the last decade, however, scientific and technological progress have made truly personalized healthcare increasingly become reality. Today’s personalized medicine involves targeted therapies and diagnostic tests. The development of targeted agents represents a major investment opportunity to pharmaceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As PM is an emerging concept, varying awareness and views are reported among a plethora of key players and stakeholders [ 62 , 63 ]. It is suggested that partnerships between scientific research bodies, regulatory agencies, politics, clinicians, pharmaceutical and diagnostic companies, and patients/public will be the key success factor [ 64 ]. No single stakeholder can set all the essential requirements to further drive the PM adoption and implementation in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…As PM is an emerging concept, varying awareness and views are reported among a plethora of key players and stakeholders [ 62 , 63 ]. It is suggested that partnerships between scientific research bodies, regulatory agencies, politics, clinicians, pharmaceutical and diagnostic companies, and patients/public will be the key success factor [ 64 ]. No single stakeholder can set all the essential requirements to further drive the PM adoption and implementation in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…While the blockbuster model represented drugs for a high-volume market, the PM model points to a smaller target group. Even though revenues might seem to reduce, the competitive advantage derived from differentiated goods actually results in increased profits driven by margins rather than volume [29]. It therefore indicates that it is possible in theory to obtain similar amount of revenue.…”
Section: Commercial Driversmentioning
confidence: 99%
“…PM, therefore, offers the industry an opportunity to increase portfolios and productivity. PM involves targeted therapies that have specific modes of action which would be very difficult for generic companies to copy [29]. Genetic sequencing as part of PM, by definition, requires that only validated biomarkers go into advanced stages of clinical trials.…”
Section: Commercial Driversmentioning
confidence: 99%
“…Stratified medicine currently relies on the use of biological markers capable of discriminating patients into sub-groups receiving the most appropriate treatment. 1,2 The recent opportunities toward this personalized patient care, especially offered by omics technologies, have transformed biomedical research. 3 Despite this, a very low proportion of discovered biomarkers or scoring systems has been transferred to clinical practice.…”
Section: Introductionmentioning
confidence: 99%